Comparative Assessment of Efficiency and Patient Tolerance of Hybrid Arch Bar, Erich’s Arch Bar and Maxillomandibular Fixation Screw Placement in Treatment of Jaw Fractures: A Prospective, Single Blinded, Parallel Group, Controlled, Clinical Study - Sherwin Samuel; Kalyani Bhate; Akash Muralidharan; Manoj Bafna; Rushab Chordia (Journal of Clinical and Diagnostic Research)
Introduction: Intermaxillary fixation, otherwise known as Maxillomandibular Fixation (MMF), is a time-tested technique used to stabilise occlusion when one or both of the jaws are fractured. There are different methods available for MMF, among which Erich’s arch bar, MMF screws, and hybrid arch bars are the most commonly used. The presence of these different methods warrants a study to evaluate the efficiency, advantages, and disadvantages of each method. Aim: To assess the efficiency and patient tolerance of hybrid arch bars, Erich’s arch bars, and MMF screw placement in the treatment of jaw fractures. Materials and Methods: This prospective, single-blinded, parallel-group, controlled clinical study was carried out in the Department of Oral and Maxillofacial Surgery at Dr. DY Patil Dental College and Hospital, Pimpri, Pune, from April 2023 to December 2023. Three parallel groups were designed with 15 participants who had mandibular fractures requiring MMF in each group. Patients in Group A were treated with Erich arch bars, patients in Group B with MMF screws, and patients in Group C with hybrid arch bars. Factors assessed included gingival inflammation on the day of removal and seven days post-removal of the MMF appliance using the modified gingival index, time taken for placement and removal in minutes, and patient discomfort using a visual analog scale. The observed values were subjected to statistical analysis using ANOVA for comparison of means and the Bonferroni test for intergroup comparison, with the significance level set at p<0.001. Results: This was a prospective, single-blinded, parallel-group, controlled clinical study conducted on 45 patients, of which 37 were male and eight were female. All patients were within the age group of 22 to 62 years. The mean value for gingival inflammation on the day of removal of MMF was highest for the hybrid arch (3.14±0.0770) and lowest for MMF screws (0.57±0.6), with a p-value <0.001. The mean value for gingival inflammation seven days post-removal of MMF was highest for Erich’s arch bar (1.57±0.732) and lowest for MMF screws (0.29±0.4), with a p-value <0.001. The mean application time was highest for Erich’s arch bar (42.36±5.2 minutes) and lowest for MMF screws (20.57±2.8 minutes), with a p-value <0.001. The mean removal time was highest for the hybrid arch bar (18.14±1.5 minutes) and lowest for MMF screws (6.93±1.4 minutes), with a p-value <0.001. The mean patient discomfort was observed to be highest with Erich’s arch bar (6.21±1.4) and lowest for MMF screws (5.00±1.4), with a p-value <0.001. Conclusion: In terms of time efficiency during the placement of appliances, gingival inflammation, and patient comfort, the best choice would be MMF screws. Although Erich arch bars consumed more time during placement, they caused less severe gingival inflammation compared to the hybrid arch bar, making them the second-best option for dentulous or partially dentulous patients whose dental arches allow for their placement.